Effect of Saccharomyces cerevisiae and Cobalt in Ammoniated Oil Palm Trunk to In-Vitro Digestibility of Dry Matter, Organic Matter and Crude Protein - Azhary Noersidiq; Yetti Marlida; Mardiati Zain; Fauzia Agustin; Fahrullah Fahrullah; Vebera Maslami (Jurnal Biologi Tropis, 2023)
Amoniated oil palm trunk has potency as feed of ruminant but have to combined with technology to increase its digestibility by supplementation with Saccharomyces cerevisiae and Cobalt (Co) minerals. The purpose of this study was to know the effect from S. cerevisiae and Co supplementation in ammoniated oil palm trunk to in-vitro digestibility of dry matter (IVDM), organic matter (IVOM) and crude protein (IVCP). This research used a 3 x 3 factorial Randomized Block Design (RBD) with 2 factors and 3 replications where factor A was the level of S. cerevisae (A1: 0%, A2: 0.5%, A3: 1%) and factor B was the level of Co (B1: 0 ppm, B2: 0.1 ppm, B3: 0.2 ppm). The results showed that supplementation of them was increased digestibility as a single factor but did not show any interaction between them. The best treatment was 0.5% S. cerevisiae and 0.1 ppm mineral Co with the highest increasion was 63.72% IVDM; 64.08% IVOM and 72.58% IVCP respectively.